ANALISIS KESESUAIAN PILIHAN PEMINATAN PESERTA DIDIK DENGAN HASIL KETETAPAN SEKOLAH - Auliani Rahmi Putri; Elni Yakub; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : A Selection of specialization becomes an important part in career development in adolescence and become important dynamics during High School. If the choice has been dropped, consequences are awaited. Some have failed or are not as expected and some are successful. The choice will lead to welfare based on the suitability of ability, talent and interest with that choice. The purpose of this study is to determine the suitability of the choice of interest of learners with the outcome of the specialization program established by the school. This research uses quantitative method with descriptive approach. Data collection techniques using documentation. To analyze data using percentages. The sample in this research is 5 classes with total of 167 students. The results of this study is that there is a suitability of the choice of learners with the results of specialization established by the school. The level of conformity of Science Development choice of students to the program of interest is higher than the level of conformity of the choice of students of Social Development towards the program of interest.Keywords: Conformity, Interest, Student Choice, Results Of School Decision.